Inflammatory and Non-Inflammatory Mechanisms Controlling Cirrhosis Development - Sánchez, Paula Sánchez; Rigual, María del Mar; Djouder, Nabil (Cancers, 2021)
Because the liver is considered to be one of the most important metabolic organs in the body, it is continuously exposed to damaging environmental agents. Upon damage, several complex cellular and molecular mechanisms in charge of liver recovery and regeneration are activated to prevent the failure of the organ. When liver injury becomes chronic, the regenerative response goes awry and impairs the liver function, consequently leading to cirrhosis, a liver disorder that can cause patient death. Cirrhosis has a disrupted liver architecture and zonation, along with the presence of fibrosis and parenchymal nodules, known as regenerative nodules (RNs). Inflammatory cues contribute to the cirrhotic process in response to chronic damaging agents. Cirrhosis can progress to HCC, the most common and one of the most lethal liver cancers with unmet medical needs. Considering the essential role of inflammatory pathways in the development of cirrhosis, further understanding of the relationship between immune cells and the activation of RNs and fibrosis would guide the design of innovative therapeutic strategies to ameliorate the survival of cirrhotic and HCC patients. In this review, we will summarize the inflammatory mechanisms implicated in the development of cirrhosis.